Chebyshev matrix polynomials and second order matrix differential equations - Defez, Emilio; Jódar, Lucas (Utilitas Mathematica, 2002)
In this paper Chebyshev matrix polynomials are introduced starting from the hypergeometric matrix function. A Rodrigues' formula, the three terms matrix recurrence relationship and orthogonality property for Chebyshev matrix polynomials are given and the differential equation satisfied by them is presented.